PENGGUNAAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KONSEP MOL - Meida Rahmi Rayantini (Universitas Lambung Mangkurat, 2016)
Abstract. Classroom action research aims to know: (1) the activity of teacher, (2) increasing the students’ activity, (3) improve the learning results of students both in cognitive and affective, (4) the students’ response. This research carried out in two cycles with total six times meeting. Each cycle consists of four stages, they are planning, implementation of action, observation and evaluation and reflection. The subject of this research is all the students of X-5 SMA Negeri 1 Bati-Bati which have 38 students, consists of 18 male students and 20 female students. In collecting data, the researcher used observation, questionnaires and test technique. The results showed that (1) the activities of teacher is very good category with 92%, (2) students’ activity increased from 80% to 93% and included in the excellent category, (3) improved students’ learning outcomes, affective learning outcomes increased from 92% to 100% and the cognitive learning results increased from 71% to 79%, (4) students’ responses to use this model are very positive.Keywords: problem solving, learning outcomes, and classroom action research